2019
DOI: 10.1080/10717544.2019.1682719
|View full text |Cite
|
Sign up to set email alerts
|

Uniform-sized insulin-loaded PLGA microspheres for improved early-stage peri-implant bone regeneration

Abstract: Poor initial stability at the first four weeks after surgery is becoming the major causes for metal implant failure. Previous attempts neglected the control release of insulin for the bone regeneration among nondiabetic subjects. The major reason may lie in the adverse effects, such as attenuated bone formation, hypoglycemia or hyperinsulinemia, that caused by the excessive insulin. Thus, spatiotemporal release of insulin may serve as the promising strategy. To address this, through solvent extraction (EMS), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In addition, the blood glucose levels of ZDF rats were checked pre‐operatively and at the time of euthanasia (7, 14, 21, and 28 days) and showed no significant difference in blood glucose levels in rats receiving either treatment, and were consistent with previous reports (Figure 2c). [ 46 ] Thus, the biocompatibility of the implants was confirmed as all rats remained healthy for the entire period of the study and showed no noticeable signs of toxicity or other adverse effects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the blood glucose levels of ZDF rats were checked pre‐operatively and at the time of euthanasia (7, 14, 21, and 28 days) and showed no significant difference in blood glucose levels in rats receiving either treatment, and were consistent with previous reports (Figure 2c). [ 46 ] Thus, the biocompatibility of the implants was confirmed as all rats remained healthy for the entire period of the study and showed no noticeable signs of toxicity or other adverse effects.…”
Section: Resultsmentioning
confidence: 99%
“…[ 55 ] Looking at the ZL rat groups, the general trend was that the addition of VD3 or INS MPs improved bone generation which is consistent with previously reported data. [ 46,56 ] Wang et al. coated similarly prepared INS MPs onto titanium screws in a rabbit mandibular defect model and found increased bone formation and pull out strength when INS was released steadily at the defect site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation rate of PLGA is mainly dependent on the ratio of glycolic acid to lactic acid monomer [45]. To obtain more detailed information on accurate regulation of the release profile of insulin-loaded particles, three kinds of uniform-sized insulin microspheres were prepared using the solvent extraction, solvent evaporation and cosolvent methods, respectively [46]. It was found that insulin-loaded microspheres prepared by the solvent evaporation method exhibited a relatively steady release rate during the first four weeks, which significantly stimulated the osteogenic differentiation of the stem cells and peri-implant bone regeneration.…”
Section: Plgamentioning
confidence: 99%
“…This bene cial effect might improve the outcome of dental implants. It was reported that local application of insulin could promote osseointegration in T2DM rats 14 . Glucagon-like peptide-1 (GLP-1) drugs also have the potential to promote osseointegration around implants 15 .…”
Section: Introductionmentioning
confidence: 99%